Cross-Protective Potential and Protection-Relevant Immune Mechanisms of Whole Inactivated Influenza Virus Vaccines Are Determined by Adjuvants and Route of Immunization - Bhide, Yoshita; Dong, Wei; Gribonika, Inta; Voshart, Daniëlle; Meijerhof, Tjarko; de Vries-Idema, Jacqueline; Norley, Stephen; Guilfoyle, Kate; Skeldon, Sarah; Engelhardt, Othmar G.; Boon, Louis; Christensen, Dennis; et al. (Frontiers in Immunology, 2019)
Adjuvanted whole inactivated virus (WIV) influenza vaccines show promise as broadly protective influenza vaccine candidates. Using WIV as basis we assessed the relative efficacy of different adjuvants by carrying out a head-to-head comparison of the liposome-based adjuvants CAF01 and CAF09 and the protein-based adjuvants CTA1-DD and CTA1-3M2e-DD and evaluated whether one or more of the adjuvants could induce broadly protective immunity. Mice were immunized with WIV prepared from A/Puerto Rico/8/34 (H1N1) virus intramuscularly with or without CAF01 or intranasally with or without CAF09, CTA1-DD or CTA1-3M2e-DD, followed by challenge with homologous, heterologous or heterosubtypic virus. In general, intranasal immunizations were significantly more effective than intramuscular immunizations in inducing virus-specific serum-IgG, mucosal-IgA and splenic IFNγ-producing CD4 T cells. Intranasal immunizations with adjuvanted vaccines afforded strong cross-protection with milder clinical symptoms and better control of virus load in lungs. Mechanistic studies indicated that non-neutralizing IgG antibodies and CD4 T cells were responsible for the improved cross-protection while IgA antibodies were dispensable. The role of CD4 T cells was particularly pronounced for CTA1-3M2e-DD adjuvanted vaccine as evidenced by CD4 T cell-dependent reduction of lung virus titers and clinical symptoms. Thus, intranasally administered WIV in combination with effective mucosal adjuvants appears to be a promising broadly protective influenza vaccine candidate. Key words: whole inactivated virus (WIV) influenza vaccines, liposome-based adjuvants, protein-based adjuvants, cross protection, non-neutralizing serum antibodies, CD4 T cells